Increasing Local Procurement By the Mining Industry in West Africa : Road-test version - World Bank (World Bank, 2012)
Regional organizations and national governments are increasingly focusing on enhancing the benefits from mining sector investment. The Africa Union's African Mining Vision 2050 outlines a new resource-based industrialization and development strategy for Africa, based on downstream, upstream, and side stream linkages, and both Economic Community of West African States (ECOWAS) and West African Economic Monetary Union (WAEMU) have developed mineral development strategies. National governments are also increasingly looking for ways to maximize benefits derived from investment in mining. This report aims to support efforts to maximize local procurement by the mining sector by providing policy recommendations for national governments and regional organizations. It also aims to provide guidance to the private sector and civil society on steps for increasing local procurement. The report takes a regional approach, driven by the potential to realize economies of scale and build on areas of competitiveness across the West African region. This document presents the outcomes of the World Bank project to support local procurement by the mining sector in West Africa. The project objectives were to (i) inform government policy related to supporting increased local procurement by the mining industry; and (ii) inform public debate/facilitate knowledge exchange between all major stakeholders, including regional organizations (ECOWAS and WAEMU), mining companies, civil society, and other supporting institutions (financial institutions, partners, training institutes, etc.). This report is the result of desk research, interviews, and analysis across West Africa, in particular in Ghana, Guinea, Senegal, Mali, and Burkina Faso; field research in Ghana, Guinea, and Senegal; research into benchmark countries; and stakeholder consultation, including three workshops held in Ghana and Guinea in September 2011. It also draws on research into global best practice. This focus on local procurement represents a shift in policy approach: rather than concentrating on the contribution by mining companies through taxes, governments are increasingly exploring ways in which mines can become more closely integrated with local economies. This report provides guidance to policymakers for setting policies and developing regulations to create a supporting framework for increasing local procurement.